Construction durable : expertise et contre-expertise d’architectes - Julie Neuwels (VertigO, 2013)
The institutionalization of sustainable development in the field of architecture leads to changes in terms of expertise. Architects have heterogeneous positions on this subject. Some, considered as experts by the public authorities, participate to the evolutions of public policies. Others doubt, even condemn, the normative orientation of these developments. By opposition they could be considered as potential experts of the expertise. Generally their doubts are discarded by the authorities that attribute them to a lack of information, or even to inertia. Trying to enlighten these differences of opinions and positions in terms of supports for public policies, the paper examines two objects: On the one hand, the implementation of the passive house certification in the Brussels energy policy; On the other hand the critics of architects who have build one or several passive buildings. The confrontation of these objects indicates a difference of apprehension of sustainable development and architecture notions.